1983
DOI: 10.1002/aja.1001680408
|View full text |Cite
|
Sign up to set email alerts
|

Quo vadis basic and clinical chronobiology: Promise for health maintenance

Abstract: Chronobiology is the eminently interdisciplinary science of interactions in time among metabolic, hormonal, and neuronal networks. It involves anatomy, biochemistry, microbiology, physiology, and pharmacology, at the molecular, intracellular, intercellular, and still higher levels of organization. The compounds coordinating a time structure--proteins, steroids, and amino-acid derivatives--provide for the scheduling of interactions among membrane, cytoplasmic, and nuclear events in a network involving rhythmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(48 citation statements)
references
References 55 publications
(49 reference statements)
1
47
0
Order By: Relevance
“…It is widely held that circadian rhythms exist in most biological systems [29] and many have been demonstrated experimen tally in dental and oral tissues [30,[31][32][33]. Okada [105] and Mimura [34] confirmed that enamel cross-striations in pig, dog, rab bit and monkey were circadian increments by using injections of NaF and lead acetate administered at known intervals.…”
Section: Daily Incremental Markingsmentioning
confidence: 88%
“…It is widely held that circadian rhythms exist in most biological systems [29] and many have been demonstrated experimen tally in dental and oral tissues [30,[31][32][33]. Okada [105] and Mimura [34] confirmed that enamel cross-striations in pig, dog, rab bit and monkey were circadian increments by using injections of NaF and lead acetate administered at known intervals.…”
Section: Daily Incremental Markingsmentioning
confidence: 88%
“…Plit et al (1) have reported elevated circulating lipid peroxides and decreased plasma concentration of vitamin E suggesting a high level oxidative stress in patients with pulmonary tuberculosis. A circadian rhythm has been well established for most laboratory variables in western population (2)(3)(4)(5)(6) …”
Section: Introductionmentioning
confidence: 99%
“…For a transfer of studies on rats to the clinic, circadian acrophase charts of human urinary variables analyzed by cosinor are available. 37 …”
Section: Discussionmentioning
confidence: 99%